Tunable Inductors Using Integrated Vanadium Dioxide Phase Change Thin Films - Liangyu Li; Weisong Wang; Eunsung Shin; Guru Subramanyam (Advances in Condensed Matter Physics)
This paper presents tunable inductors designed with vanadium dioxide (VO2) thin film to implement tunability. Two types of configurations, a single line coil inductor and a dual line coil inductor, are proposed. Tunable inductance is realized by thermally controlling VO2 thin film stub to be an insulator or a conductor. The measurements of inductors are taken in the frequencies range from 0.01 GHz to 10 GHz. The electrical model has been developed to derive the corresponding inductance. The results show that the tuning range is about 69% when the temperature changes from room temperature to above the critical temperature of 68°C.